2020
DOI: 10.1111/jphd.12423
|View full text |Cite
|
Sign up to set email alerts
|

Caries disparities among Medicaid‐enrolled young children from pediatric primary care settings

Abstract: Objectives: The objectives of this study are to determine the overall and racial differences in the extent of caries experience and to examine the association between child and parent/caregiver characteristics and caries among 3-6-yearold Medicaid-enrolled children. Methods: This study reports baseline cross-sectional data from a larger pragmatic clinical trial in pediatric primary care practices. Child-level clinical dental exams included decayed and filled teeth (dft) using ICDAS criteria and parent/ caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Two researchers screened and evaluated the full text of 20 articles, and finally 15 articles were included (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). As shown in Figure 3, all the included studies were within the triangle area, and no obvious bias was observed (Figure 3).…”
Section: The Included Studiesmentioning
confidence: 99%
“…Two researchers screened and evaluated the full text of 20 articles, and finally 15 articles were included (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). As shown in Figure 3, all the included studies were within the triangle area, and no obvious bias was observed (Figure 3).…”
Section: The Included Studiesmentioning
confidence: 99%
“…Sociodemographic variables were collected via a baseline questionnaire completed by parent self-report at the WCV encounter from which they and their child were recruited. These variables in the questionnaire were adapted from the National Health and Nutrition Examination Survey, and items collapsed into fewer categories as follows: child and parent sex (male or female), child race (American Indian or Alaska Native, Asian, Hawaiian or Pacific Islander, White, and >1 race were collapsed to “non-Black,” while Black or African American was “Black” for analysis [races were collapsed into non-Black and Black because, with the exception of White children, sample sizes of races were too small to handle individually, and there is prior literature indicating disparities in caries experience among Black children compared with non-Black children 22 ]), child ethnicity (Hispanic or non-Hispanic), child age in years, parental educational attainment (grades 7-9, grades 10 and 11, and high school diploma or General Educational Development certification were collapsed as “≤high school,” while associate’s degree or some college, college or university degree, some graduate school, and graduate degree were collapsed for analyses to “>high school”), and parental marital status (common law, divorced, separated, single, and widow were collapsed for analyses as “not married,” while “married” was a category by itself). The questionnaire also addressed oral health behaviors, including whether the child had ever visited a dentist (yes or no) and, if so, at what age (in years) the child had their first dental visit.…”
Section: Methodsmentioning
confidence: 99%
“…Racially minoritized school-going children, particularly those from low-income families, including African Americans [Selvaraj et al, 2021], Hispanics [Matsuo et al, 2015], Indigenous or native populations [Grim et al, 1994;Nath et al, 2021b], have a higher dental caries prevalence than their white privileged counterparts. Racially minoritized children are defined as "individuals and populations, including numerical majorities, whose collective cultural, economic, political and social power has been eroded through the targeting of identity in active processes that sustain structures of hegemony" [Selvarajah et al, 2020].…”
Section: Introductionmentioning
confidence: 99%